2009
DOI: 10.1021/es802634y
|View full text |Cite
|
Sign up to set email alerts
|

Forest Fire Effects on Mercury Deposition in the Boreal Forest

Abstract: Particulate Hg (pHg) is a component of smoke from biomass burning and has the potential for local redeposition. Throughfall (precipitation collected beneath a conifer or deciduous canopy) and open precipitation samples were collected pre- and postfire in 2005 and 2006 using passive precipitation collectors across the Superior National Forest, located in northern Minnesota, USA. Samples were collected approximately every two weeks and analyzed for total Hg (THg) and methyl Hg (MeHg). THg concentrations increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 25 publications
1
54
1
Order By: Relevance
“…4), which may reflect atmospheric deposition of Hg p prior to erosion of sediments. Witt et al (2009) reported total Hg levels in precipitation significantly increased following fires (samples collected 3-47 days postburn). Since Hg p is readily scavenged by rain, these results suggested Hg released from vegetation and soil during a fire was deposited through wet deposition of Hg p .…”
Section: Atmospheric Deposition Of Hg Pmentioning
confidence: 97%
“…4), which may reflect atmospheric deposition of Hg p prior to erosion of sediments. Witt et al (2009) reported total Hg levels in precipitation significantly increased following fires (samples collected 3-47 days postburn). Since Hg p is readily scavenged by rain, these results suggested Hg released from vegetation and soil during a fire was deposited through wet deposition of Hg p .…”
Section: Atmospheric Deposition Of Hg Pmentioning
confidence: 97%
“…Combustion studies in laboratories on conifer and deciduous litter have indicated that nearly the entire Hg pool (>98%) is emitted back to the atmosphere, with little left behind in ash (Friedli et al, 2003). Although the bulk of the Hg emitted during wildfires is in elemental form (Hg 0 ) that will ultimately be deposited outside the watershed and potentially far from the site of the fire, about 13% of the Hg emitted during wildfires is in particulate form (Friedli et al, 2003), which has the potential to be deposited locally (Witt et al, 2009). In our study, 72% of the Hg pool was lost from the forest floor, 7% from the 0-to 10-cm soil depth and 10% from the 10-to 20-cm soil depth.…”
Section: S63mentioning
confidence: 99%
“…Hence, volatilization of C and associated THg as a result of fire could lead to long-term decreases in Hg in the aquatic food chain as THg is removed from the watershed; however, short-term impacts are less clear. Other studies in northern Minnesota have indicated that fire leads to enhanced local deposition (Witt et al, 2009) that, in the short term, has the potential to bioaccumulate in the food chain (Kelly et al, 2006). Others have found little or no change in accumulation in aquatic biota following fire Carignan, 1999, 2000;Allen et al, 2005).…”
mentioning
confidence: 99%
“…Comparison to other studies suggests that the vast majority of this loss is to the atmosphere, leading to both long-range transport and localized increases in atmospheric mercury and deposition in other watersheds. 31 Although it is likely that these disturbances increase the hydrologic mobility of Hg from soils, this flux is most likely small (10−20%) compared to fluxes to the atmosphere. Because the combination of blowdown, salvage logging, and wildfire dramatically decreased both THg concentrations and pools, it may take decades, perhaps centuries, for Hg to accumulate to predisturbance levels, 30 which could decrease Hg levels in nearby aquatic biota over this time period.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%